Diagnóstico inicial al balance a 31 de diciembre del año 2013 para la implementación de NIIF en la Cooperativa Multiactiva de Hogares de Bienestar “Coohobienestar" (2014)
The research project "Diagnostic initial balance at December 2013 multiactive cooperative welfare homes 31 Coohobienestar" is conducting a study and analysis of each of the accounts and items included in the balance sheet of the cooperative multiactive homes Coohobienestar welfare of the city of Armenia in order to determine each a current state, allowing us to elucidate the level of impact that the process of conversion to international accounting standards may have on each cite the specific rule which should go in the conversion to IFRS on these items and make an appropriate recommendation for this process, which is set as mandatory for SMEs in Decree 3022 of 2013.